Sustainable development on water resources management, policy and governance in a changing world - Wan, Zhanhong; Wan, Rongrong; Ahmad, Sajjad; Eyvaz, Murat (Frontiers Media Sa, 2023)
[No abstract available]
Keywords: sustainable development; water resources management; water resources policy; water resources governance; sustainability